A flexible mesoporous Cu doped FeSn-G-SiO2 composite based biosensor for microalbumin detection - Areerob, Yonrapach; Chanthai, Saksit; Oh, Won Chun (My University, 2022)
A new mesoporous Cu-doped FeSn-G-SiO2 (CFSGS) based biosensor was developed for the detection of microalbumin in urine samples. The mechanically flexible FeSn modified sensor was fabricated at room temperature. These demonstrations highlight the unexplored potential of FeSn for developing novel biosensing devices. It is extremely sensitive and selective. Surfactant-aided self-assembly was used to synthesise the mesoporous CFSGS. The large surface area due to the mesopore presence in the CFSG surface that has been composited inside the mesoporous SiO2 boosted the electrochemical detection. The linear range and detection limit of microalbumin under optimum circumstances were 0.42 and 1 to 10 μL, respectively. This easily fabricated mesoporous CFSGS provided a fast response with high sensitivity, and good selectivity. The sensor's reusability and repeatability were also quite high, with just a 90 percent drop after 4 weeks of storage at ambient temperature. The biosensor also demonstrated high selectivity against typical potential interfering chemicals found in urine (ascorbic acid, urea, and sodium chloride). The good performance of the mesoporous CFSGS biosensor was validated by measuring microalbumin, and the findings indicated that this sensing device performed very well.